Competency Development Strategy for Management Trainee Programs at Sharia Banking in Indonesia - Sofiyah, Sofiyah; Kartika, Lindawati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study aims to develop competency strategies in the sharia banking sector to align with industry needs, addressing the high unemployment rate among Indonesia’s 20–24 age group (2,527,741 people) caused mainly by a skills mismatch. With the sector recording 15.6 percent yoy asset growth, sharia banking offers strong potential to absorb young talent. Methodology/approach – The research applies the Analytical Hierarchy Process (AHP) and descriptive analysis to identify key competencies, priority areas, and strategic actions for talent development in sharia banking. Findings – Knowledge, particularly in sharia banking, is the top priority competency, with HR Directors as the main decision-makers and building competitive leadership teams as the ultimate goal. The highest-ranked strategy is creating a positive work culture. Descriptive results highlight the importance of sales skills, experiential learning, and active mentoring as critical components of talent development. Novelty/value – This study provides the foundation for a management trainee program designed to produce young leaders who are competent, adaptable, and grounded in sharia values through an integrated learning process combining assessment, field practice, intensive mentoring, and career mapping.